Transforming food systems in the Global South: a radical approach - Suarez, Andres; Ume, Chukwuma (Frontiers in Sustainable Food Systems, 2024)
Sustainability within food systems (FS) transcends approaches that only consider FS transformation via changing agricultural practices or consumption patterns. The essence lies in addressing the root causes of current unsustainable FS and their associated social and environmental ramifications. This paper aims to outline the solutions needed to revamp these challenges, by paying special attention to the state-capital nexus in the context of the FS’global core-periphery dialectics. Thereby, we embrace radical political agroecology as being essential in promoting sustainability within the FS, especially in the Global South. Agroecology is proposed as the strategy to address the food system’s complexity in terms of the social, environmental, and economic embeddedness. We conclude with potential solutions that contribute to the pathway for FS sustainability.